19 Maintaining the benefits of initial cardiac rehabilitation in heart failure patients: a mixed methods systematic review. (21st November 2022) - Seago-Gilbert, Andi; Jones, Arwel Wynn; Curtis, Ffion; Henderson, Hannah; Siriwardena, Aloycious Niro
Abstract : Background: The most effective way to maintain benefits of cardiac rehabilitation (CR) in adults with heart failure remains unclear. Aim: The aim of this systematic review was to synthesise available evidence on the efficacy of interventions following cardiac rehabilitation and understand patient experience. This abstract reports on the experience of adults with heart failure following cardiac rehabilitation. Methods: Electronic databases (MEDLINE, CINAHL, EMBASE, AMED, PEDro, CENTRAL) and trial registers (ClinicalTrials.gov) were searched from inception to January 2022. Search results were screened for qualitative studies reporting experiences of following cardiac rehabilitation. Thematic synthesis involved line-by-line coding of the findings of included studies, development of descriptive themes, and generation of analytical themes. Study quality was assessed using CASP. Results: Five eligible qualitative studies were identified (1=questionnaire and semi-structured, 2=semi-structured interviews, 1=focus groups and semi-structured interviews, 1= focus groups), with a total of 112 participants. Thematic synthesis generated 18 themes as influential to maintaining benefits of cardiac rehabilitation in heart failure. These organised into 5 analytical themes, including credible sources of specialist and social support, sense of safety and solidarity, biofeedback, and outcomes of behaviour, positive versus negative attitudes about exercise with heart failure and access to appropriate physical resources and environment ( figure 1 ). All studies were clear in research aims and appropriate qualitative methodology, but not if the researcher role, potential bias and influence were critically examined. Conclusion: There is currently no gold standard approach to maintaining benefits of cardiac rehabilitation and a variety of approaches exist worldwide. Patients have unique needs and preferences which change over time depending on their condition, therefore it is important to involve patients in collaboration with healthcare professionals. This systematic review highlights interventions which consider attitudes towards exercise with heart failure and include longer term, supervised, structured and tailored support are worthwhile strategies following cardiac rehabilitation.